Erythropoietin inhibits HIF-1α expression via upregulation of PHD-2 transcription and translation in an in-vitro model of hypoxia ischemia - Souvenir, Rhonda (2013)
Hypoxia inducible factor (HIF)-1α is the central transcriptional factor for the regulation of oxygen-associated genes in response to hypoxia. Erythropoietin (EPO), a hematopoietic growth factor, increases oxygen availability during hypoxia/ischemia and is associated with neuroprotection following hypoxia ischemia in laboratory models of stroke. However, EPO has failed to translate in a clinical setting. Thus it is critical to elucidate the key players in EPO-induced neuroprotection. Our preliminary studies have shown that EPO, as a downstream gene of hypoxia inducible factor (HIF), inhibits HIF-1α in a dose-dependent manner in an in-vitro model of hypoxia ischemia. This study is designed to elucidate the primary mediator of EPO-induced HIF-1α inhibition and subsequent cell survival/neuroprotection. Oxygen and glucose deprivation (OGD) of nerve growth factor (NGF) differentiated rat pheochromocytoma (PC-12) cells were used to model hypoxia ischemia in an in vitro environment. The profile of HIF-1α, HIF-2α and PHD-2 expression, HIF-1α and prolyl hydroxylase (PHD-2) mRNA levels, MMP-9 and cell death was evaluated in the presence and absence of either EPO or PHD-2 inhibitor during OGD. Our findings showed that EPO treatment resulted in an increase in PHD-2 transcription and translation, inhibition of HIF-1α expression, reactive oxygen species (ROS) formation and matrix metalloproteinase (MMP)-9 activity, resulting in increased cell survival after OGD. We also observed that EPO-induced cell survival/neuroprotection was reversed by siRNA silencing of PHD-2. This led to the conclusion that PHD-2 is a key mediator of EPO-induced HIF-1α inhibition and subsequent neuroprotection in an in vitro model of hypoxia ischemia.